1969
DOI: 10.12669/pjms.322.8731
|View full text |Cite
|
Sign up to set email alerts
|

Doctors; A Neglected Clientele When It Comes to Screening, Diagnosis and Management of Mental Health Issues Like Anxiety and Depression

Abstract: Objectives:To analyze prevalence of anxiety and depression among doctors serving in a tertiary care hospital in Lahore, with a study of impact of relevant demographic features.Methods:A cross sectional study was conducted at Combined Military Hospital, Lahore, from February 2014 to Jan 2015. Participants were doctors serving in subject hospital for at least six months duration. Standardized Hospital Anxiety Depression Score (HADS) inventory was selected as inventory. Formal approval from hospital ethical commi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 8 publications
5
21
0
Order By: Relevance
“…One of the study findings shows that role insufficiency among doctors had the strongest association with depressive symptoms [ 21 ]. This was supported by a study reported on the years of services that are shown to has a significant association with depression [ 22 ]. Meanwhile, anxiety among doctors was associated with the inappropriate judgment made by the doctors due to emotional exhaustion and reduce sleep quality [ 23 ].…”
Section: Introductionmentioning
confidence: 52%
“…One of the study findings shows that role insufficiency among doctors had the strongest association with depressive symptoms [ 21 ]. This was supported by a study reported on the years of services that are shown to has a significant association with depression [ 22 ]. Meanwhile, anxiety among doctors was associated with the inappropriate judgment made by the doctors due to emotional exhaustion and reduce sleep quality [ 23 ].…”
Section: Introductionmentioning
confidence: 52%
“…Though data assessing the effect of the recent pandemic on mental health of doctors is sparse especially in the developing countries, but a previous survey in 2016 among doctors working in a tertiary care hospital in Pakistan reported an association of female gender and more service years with anxiety and depression [ 12 ]. Even among the general population depression and anxiety related disorders are found to be more common among females [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, patients were encouraged to stay at home if symptoms are not severe, hence frontline doctors may have less duties to attend. It is already known that social network structure and function are strongly intertwined with anxiety and depressive symptoms [ 12 ], therefore it is possible that doctors who are working less than 20 h a week are more likely to be distressed due to unusually less work and less social interaction. This may be compounded by feelings of guilt of leaving colleagues to work instead of them [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 However, other studies from Pakistan reported relatively higher level of anxiety symptoms among; women in a lower middle class semi-urban community, women with infertility, women with polycystic ovary syndrome, patients suffering from tuberculosis, and doctors serving in a tertiary care hospital. 20 - 24 …”
Section: Discussionmentioning
confidence: 99%